Girls and Schools in Sub-Saharan Africa : From analysis to action - Odaga, Adhiambo; Heneveld, Ward. (Washington : World Bank, 1995)
This study provides a summary of the state of knowledge of the factors constraining girls' schooling in Sub-Saharan Africa. It also presents an outline of how this accumulated knowledge can be used in practical ways to facilitate the design of programs to accelerate female participation in education in the region. It further discusses some promising international experiences and strategies to enhance girls' schooling.
Includes bibliographical references (p.[98]-112).
ne 7/03/2018
Loan
Keywords: Women; Women; Girls; School environment; Education